(untitled) - Monroe, James S. (Australia, 2007)
Physical geology explorring the earth, Sixth Edition, doesn't just explain physical geology and its processes; it places that knowledge within the context of human experience by consistently emphasizing relevance, resources, and the environment
Keywords: Physical geology,Vật lý đất đá; Textbooks,Sách giáo khoa